Effect of Using the Hydrostatics and Heat Kit on High School Students Conceptual Change in the Heat Topic - Yulisa Baks; Asri Arbie; Trisnawaty Junus Buhungo (Jurnal Pijar MIPA, 2026)
This research is motivated by the fact that students frequently experience misconceptions, particularly in distinguishing between temperature and heat, understanding the direction of heat transfer, and analyzing the relationship between heat and phase changes. This study aims to analyze the effect of using the Hydrostatics and Heat Kit on senior high school students’ conceptual change in the topic of heat. The use of the Hydrostatics and Heat Kit in heat instruction is expected to facilitate students’ conceptual understanding through concrete and direct experimental activities. This study employed an experimental method with a one-group pretest–posttest design conducted at SMA Negeri 1 Bolangitang. The research subjects consisted of two classes: an experimental class and a replication class, each with 30 students. A Three-Tier Diagnostic Test was used as the research instrument to identify students’ conceptual status, which was classified into Guessing (MB), Lack of Conceptual Understanding (TPK), Misconception (M), and Scientific Understanding (PK). Data were analyzed using descriptive quantitative analysis by comparing pretest and posttest results to identify patterns of students’ conceptual change. These patterns were represented by red arrows (↑) indicating improvement from misconception to scientific understanding, blue arrows (↓) indicating a decline in conceptual understanding, and yellow circles (O) indicating no conceptual change. The results showed that students in both classes experienced conceptual changes toward more scientific understanding, as indicated by the dominance of red arrows (↑). The most significant improvements occurred in differentiating between temperature and heat and in analyzing the relationship between heat and temperature changes during phase transitions. These findings support the Constructivism Conceptual Change theory, which emphasizes learning as a process of reconstructing initial conceptions into more accurate scientific concepts. Overall, the use of the Hydrostatics and Heat Kit within an Inquiry-Based Learning framework was effective in improving students’ conceptual understanding and reducing misconceptions about heat.